Reusable hybrid foam catalyst for hydrolytic dehydrogenation of amine adducts of borane: Porous PVA-Immobilized Co-Ru nanoparticles - Genis, Dilek; Filiz, Bilge Coskuner; Depren, Serpil Kilic; Figen, Aysel Kanturk (ELSEVIER, 2020)
In this study, reusable hybrid foam catalyst was synthesized, based on reduction of cobalt and ruthenium ions into polyvinyl alcohol (Co-Ru/PVA), for hydrolysis of ammonia borane (NH3BH3, AB) and its derivative methylamine borane, (CH3NH2BH3, MeAB), to generate hydrogen. Sixteen different hybrid catalysts were synthesized under different preparation conditions. The effect of different independent variables such as reduction medium and temperature, solvent, and post-treatment on hydrogen evolution rate as a dependent variable was evaluated using the Analysis of Variance (ANOVA). It was found that Co-Ru/PVA-16 was exhibited the highest catalytic activity for the NH3BH3 hydrolysis reaction based on the statistical analysis observations. The Co-Ru/PVA-16 hybrid catalyst was characterized by several advance techniques as X-ray diffraction (XRD), X-ray photoelectron electron spectroscopy (XPS), high-resolution transmission electron microscopy (HR-TEM), scanning electron microscopy (SEM), inductively coupled plasma mass spectrometry (ICP-MS) and Fourier transform Infrared spectroscopy (FT-IR). High initial turnover frequency (TOF) of 3384.23 mol(H2)mol(CoRu)(-1)min(-1) and 346.16 mol(H2)mol(CoRu)(-1)min(-1) were reported for NH3BH3 and CH3NH2BH3 hydrolysis, respectively. Besides high catalytic activity, Co-Ru/PVA-16 hybrid catalyst was reused in the hydrolysis of NH3BH3 over 46 cycles without decrease in H-2 evolution rate.
Keywords: Ammonium borane; Methylamine borane; Hydrolysis; Foam; Hybrid catalyst; Cobalt; Ruthenium; ANOVA; POLYMER-SUPPORTED RHODIUM; AMMONIA BORANE; HYDROGEN GENERATION; SHELL NANOPARTICLES; METHYLAMINE-BORANE; BY-PRODUCT; METAL; GRAPHENE; REDUCTION; Chemistry; Science & Technology - Other Topics; Materials Science